2000
DOI: 10.1016/s0895-9811(00)00053-5
|View full text |Cite
|
Sign up to set email alerts
|

The Las Matras tonalitic–trondhjemitic pluton, central Argentina: Grenvillian-age constraints, geochemical characteristics, and regional implications

Abstract: The N-S trending belt with Grenvillian-age rocks developed in central western Argentina represents the basement of an allochthonous terrane derived from Laurentia during the Early Paleozoic. The Las Matras pluton (36Њ46 H S, 67Њ07 H W) is located at the southern extension of this belt in the Las Matras Block. It consists of a low-Al tonalitic to trondhjemitic facies characteristic of an arc magmatism. Isotopic studies yielded Grenvillian Rb-Sr (1212^47 Ma) and Sm-Nd (1188^47 Ma) ages which, due to the undeform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 59 publications
4
49
0
8
Order By: Relevance
“…Similarity of Pb isotope ratios between the xenoliths of the Precordillera and rocks of the extensive Grenvillian age-equivalent belts throughout Gondwana cannot be ruled out because such comparisons were not made by Kay et al [22], and, in fact, Wareham et al [43] reported close similarity of Pb and Nd isotope characteristics of Grenvillian-age rocks of Laurentia and the Precordillera to Mesoproterozoic rocks in East and West Antarctica, Natal, and the Falkland Islands. A recent isotopic study of Grenvillian-age basement in the southern part of the western Sierras Pampeanas reveals signi¢cant isotopic di¡erences from the Laurentian Grenville [44]. Thus, the widely held assumption of dominantly Grenvillian-age basement of Laurentian af¢nity for the Precordillera may be untrue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarity of Pb isotope ratios between the xenoliths of the Precordillera and rocks of the extensive Grenvillian age-equivalent belts throughout Gondwana cannot be ruled out because such comparisons were not made by Kay et al [22], and, in fact, Wareham et al [43] reported close similarity of Pb and Nd isotope characteristics of Grenvillian-age rocks of Laurentia and the Precordillera to Mesoproterozoic rocks in East and West Antarctica, Natal, and the Falkland Islands. A recent isotopic study of Grenvillian-age basement in the southern part of the western Sierras Pampeanas reveals signi¢cant isotopic di¡erences from the Laurentian Grenville [44]. Thus, the widely held assumption of dominantly Grenvillian-age basement of Laurentian af¢nity for the Precordillera may be untrue.…”
Section: Discussionmentioning
confidence: 99%
“…The ignimbrites overlie the basement integrated by igneous and metamorphic rocks of Late Proterozoic to Early Paleozoic age (Linares et al 1980;Tickyj et al 1999;Sato et al 2000).…”
Section: Geological Settingmentioning
confidence: 99%
“…Matras, ocorre uma faixa N-S de rochas de idades mesoproterozóicas grenvilianas, pertencentes ao embasamento do Terreno Cuyania (Sato et al, 2000). Incluem as serras de Toro Negro, Umango, Maz e Espinal ao norte; Sierra de La Huerta/Sierra…”
Section: Ao Longo Das Sierras Pampeanas Ocidentais Até Os Blocos De Sunclassified
“…Valle Fértil e Sierra de Pie de Palo na porção central; e blocos de San Rafael e Las Matras ao sul (Sato et al, 2000) (Figura 1).…”
Section: Ao Longo Das Sierras Pampeanas Ocidentais Até Os Blocos De Sunclassified
See 1 more Smart Citation